PENGARUH PENDAPATAN PER SAHAM DAN PENGEMBALIAN EKUITAS TERHADAP HARGA SAHAM PT UNILEVER INDONESIA Tbk - Nabila Ramadhesinta; M. Kausar Maulana (Jurnal Ekonomi dan Industri, 2023)
The purpose of this study is to analyze the effect of earning per share and return on equity on share price at PT Unilever Indonesia Tbk. This research was conducted at companies engaged in the Consumer Goods Industry sector, namely PT. Unilever Indonesia Tbk. The data used in this study is secondary data consisting of quarterly financial reports. Besides that, data on the closing stock price of PT. Unilever Indonesia, Tbk. The analytical method uses multiple and simple linear regression analysis. The results of the study are as follows: 1) Earning per share and return on equity together have a significant effect on stock prices at PT. Unilever Indonesia Tbk 2) Earning per share has a positive and significant effect on stock prices. 3) Return on equity has an effect but not significant on stock prices.